2020
DOI: 10.1080/13557858.2020.1841120
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 among Black women: evaluating perspectives and sources of information

Abstract: Objectives: Coronavirus disease 2019 (COVID-19) has burgeoned into a pandemic that highlights the countless social and health disparities that have existed in Black communities within the United States for centuries. Recent epidemiological data show that Black communities are being disproportionately impacted by COVID-19, resulting in higher morbidity and mortality rates compared to other racial and ethnic groups. For Black women in particular, a longstanding history of systemic racism and marginalization has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 30 publications
3
53
0
2
Order By: Relevance
“…Recent studies from the US have highlighted similar issues of mistrust in healthcare and government among African Americans, 27 with decades of racism, marginalisation and discrimination isolated communities and making them particularly vulnerable and susceptible to COVID-19. 28,29 Our work is the first to emphasise the impacts of this historical mistrust on the UK test, trace and isolate systems. It is vital that consistent efforts are made to work with community champions and leaders during and beyond the pandemic, to start to shift and reframe beliefs, towards a more positive narrative that positions institutions such as the NHS as being equally welcoming and there for everybody.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies from the US have highlighted similar issues of mistrust in healthcare and government among African Americans, 27 with decades of racism, marginalisation and discrimination isolated communities and making them particularly vulnerable and susceptible to COVID-19. 28,29 Our work is the first to emphasise the impacts of this historical mistrust on the UK test, trace and isolate systems. It is vital that consistent efforts are made to work with community champions and leaders during and beyond the pandemic, to start to shift and reframe beliefs, towards a more positive narrative that positions institutions such as the NHS as being equally welcoming and there for everybody.…”
Section: Discussionmentioning
confidence: 98%
“…So, even though they had symptoms, they were very reluctant to go, because they were worried that they might not have it, but by exposing themselves to people at the test centre that have it, that they themselves will catch it. (Ivorian, Female, 29) Majority of participants also expressed they lacked the necessary knowledge and skills required to access the testing-booking system, with limited IT skills and access to smart devices.…”
Section: Self-efficacy An Antidote To Fear and Stigmamentioning
confidence: 99%
“…COVID-19 and associated public health restrictions have had a profound impact on the physical and socioemotional health of mothers and families around the globe [ 9 , 10 ], including those who have given birth or navigated postnatal services during the pandemic [ 11 , 12 ]. Physical distancing and changes in health service provision has disrupted healthcare access for peri- and postnatal women, with non-essential appointment cancellations, new personal protective equipment requirements, and in some instances, a transition to virtual care [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…12,19,50,51 Women in our study described the stresses and pressures they faced as a result of decreased informal support, increased childcare and homeschooling demands, and the closures/restrictions of valuable support services (e.g., doulas)-all of which have been reported in other literature with non-newcomer women. 10,14,19 These stressors were coupled with feelings of disappointment and loss related to missed or robbed birth-and postnatal-related moments and milestones. 14,16,19 Studies with non-newcomer women have also found signi cant increases in postpartum anxiety 12 and depression symptoms 52 during the pandemic, in addition to a signi cant increase in healthcare visits for postpartum mental health concerns.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Positive socioemotional supports in the postpartum period help to mitigate against depressive symptoms and improve maternal self-e cacy. 6,8 COVID-19 and associated public health restrictions have had a profound impact on the physical and socioemotional health of mothers across the globe, 9,10 including those who have given birth or navigated postnatal services during the pandemic. 11,12 Physical distancing and changes in health service provision has disrupted healthcare access for peri-and postnatal women, with non-essential appointment cancellations, new personal protective equipment requirements, and in some instances, a transition to virtual care.…”
Section: Introductionmentioning
confidence: 99%